2014
DOI: 10.1111/flan.12076
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Foreign Accent: Extended Stays Abroad, Level of Instruction, and Motivation

Abstract: Studies have examined various factors that affect pronunciation including phonetic context, style variation, first language transfer, and experience abroad. A plethora of research has also linked motivation to higher levels of proficiency in the second language. The present study uses native speaker ratings and multiple regression analysis to investigate the relationship between motivation, cultural sensitivity, and level of instruction with perceived foreign accent. Participants include adult learners of Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 32 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…A great deal of research has investigated tracking and shadowing in controlled contexts as techniques for improving listening comprehension (Hamada, ), intonation (Hsieh, Dong, & Wang, ), and prosody, fluency, and rhythm when reading aloud (Harmon, ). However, they have been studied only minimally as a tool for improving L2 learners’ pronunciation in spontaneous speech (Foote, ; Martinsen, Alvord, & Tanner, ).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of research has investigated tracking and shadowing in controlled contexts as techniques for improving listening comprehension (Hamada, ), intonation (Hsieh, Dong, & Wang, ), and prosody, fluency, and rhythm when reading aloud (Harmon, ). However, they have been studied only minimally as a tool for improving L2 learners’ pronunciation in spontaneous speech (Foote, ; Martinsen, Alvord, & Tanner, ).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Thus, such research cannot be generalized to the improvement of pronunciation in spontaneous speech, and its generalizability to learners of languages other than English, including learners in K–12 settings, is further limited by the fact that much of it has been conducted with adult learners of English (Eckstein, ; Foote, ; Lee et al, ; Ma, ). Furthermore, the little empirical evidence that does exist suggests that technology‐infused approaches that engage learners in imitative techniques such as shadowing and tracking could prove beneficial (Foote, ; Martinsen et al, ). Framed by this body of previous work, this study examined the effect of such activities on L2 pronunciation, using the following research questions: To what extent do high school French students who engage in computer‐based shadowing and tracking exercises over the course of a term exhibit changes in their L2 pronunciation in either controlled and/or spontaneous speech? To what extent do students find the exercises helpful?…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Prior research has shown that once learners reach a certain level of comprehensibility, their progress towards native-like norms tends to slow (Martinsen, Alvord & Tanner, 2014). First, the 4-5 range effectively represents the middle range of comprehensibility in the scale used in this study, since no student in either course received an average rating lower than 2.…”
Section: Resultsmentioning
confidence: 99%
“…That is, tools for cooperative work are not provided nor it is systematically promoted the communication between teacher-student and student-student. Researches of Martinsen, Avord and Tanner (2014) have shown the benefits of interaction for improving the pronunciation of foreign languages. However, despite this limitation, the user can set changes in the accent of the searches by clicking the "mora" of the results provided by the "Prosody Tutor Suzuki-kun" function.…”
Section: Section 4: Interactivitymentioning
confidence: 99%
“…
Most of the studies focus on the teaching of foreign languages indicate that little attention is paid to the prosodic features both didactic materials and teaching-learning processes (Martinsen, Avord and Tanner, 2014). In this context and throughout this article, an analysis of the didactical and technical dimensions of OJAD (Japanese Accent Online Dictionary) is performed, linked to a project of the National Institute for Japanese Language and Linguistics led by Minematsu (University of Tokyo).
…”
mentioning
confidence: 99%